2009
DOI: 10.1038/onc.2009.409
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1 receptor, a target and regulator of estrogen receptorα action, mediates the proliferative effects of estradiol in breast cancer

Abstract: Estrogen receptor-α (ERα) and its ligand estradiol (E2) play critical roles in breast cancer growth and are key therapeutic targets. Here, we report a novel dual role of the adenosine A1 receptor (Adora1) as an E2/ERα target and a regulator of ERα transcriptional activity. In ERα-positive breast cancer cells, E2 up-regulated Adora1 mRNA and protein levels, an effect that was reversed by the E2 antagonist ICI 182,780. siRNA ablation of Adora1 in ERα-positive cells reduced basal and E2-dependent proliferation, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 41 publications
1
42
0
Order By: Relevance
“…These effects could be partially inhibited by using A1R antagonist. In contrast, a study by Lin et al [13] showed that A1R antagonist reduced proliferation in MCF-7 cells. Furthermore, knockdown of A1R by siRNA decreased cell proliferation, but over-expression of A1R could increase cell proliferation.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…These effects could be partially inhibited by using A1R antagonist. In contrast, a study by Lin et al [13] showed that A1R antagonist reduced proliferation in MCF-7 cells. Furthermore, knockdown of A1R by siRNA decreased cell proliferation, but over-expression of A1R could increase cell proliferation.…”
Section: Introductionmentioning
confidence: 73%
“…It has been documented that the A1R agonist could inhibit cell proliferation in colonic cancer, astrocytoma and melanoma cells [9, 10, 17]. In contrast, several studies also showed that the A1R antagonists could reduce cell proliferation [13, 18]. Notably, a combined treatment with A1R agonist and temozolomide significantly inhibited cell proliferation and promoted apoptosis compared to temozolomide alone in cancer stem cells [19], whereas A1R antagonist DPCPX was found to significantly induce apoptosis in MCF-7 cells [18].…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, adenosine is appreciated for its complex role in many nervous system disorders such as alcoholism, epilepsy, traumatic brain injury, ischemia, anxiety, Alzheimer’s disease, Parkinson’s, and brain cancer [2,3,4,5,6,7,8]. Although progress has been made in understanding adenosine’s role in certain pain states, less is known about how it is involved in migraine [9].…”
Section: Introductionmentioning
confidence: 99%
“…The activation of A1 adenosine receptors may thus contribute to resistance against trastuzumab (Herceptin) therapy, which relies on p27 upregulation (Lane et al, 2001). A1 adenosine receptor has also recently been shown to act as a target and regulator of estrogen receptor-a in breast cancer cells (Lin et al, 2010).…”
Section: Purinergic Signaling In Cancermentioning
confidence: 99%